Aeroelastic assessment of distributed electric propulsion wings. Issue 1 (1st February 2022) - Memmolo, V.; Marano, A. D.; Maio, L.; Nicolosi, F.; Marulo, F.
Abstract: During recent years, aircraft manufacturers focused on environmentally friendly and aerodynamically efficient aircraft concepts that could allow a radical reduction of emissions. The use of a hybrid-electric powertrain is one of the most effective ways to design near-zero-emission aircraft. These aircraft are highly performing and sophisticated so the design process must be extremely accurate. Among the various innovative aspects, the use of distributed engines to improve aerodynamic performance poses new challenges from a structural perspective due to the tip-mounted propeller demanding a complicated design due to reduced flutter performance. This results in higher stiffness requirements and consequently increased mass. Both the weight penalty needed to prevent dynamic instability, and the wing aeroelastic tailoring, crucial to minimize such an additional weight, is of utmost importance. Because of setting up a preliminary approach to estimate the static and dynamic effects of such a non-conventional wing architecture, the present paper shows a comprehensive structural analysis of a wing opportunely designed according to certification specification and equipped with a variable position powertrain. Several different engines are then moved along the wingspan to estimate how it affects the dynamic response using a simplified beam-stick finite element model. The results show that the engine position strongly affects the flutter velocity with a particular band bell curve over the wingspan with the maximum in between 60-70% wingspan. In addition, it is worth noting how the tip propeller may cause a reduction of flutter velocity with respect to the conventional configuration with the turbine mounted in between 30-40% wing-span.